Procedure of stochastic approximation for the diffusion process with semi-Markov switchings - Rosa, V.; Chabanyuk, Ya. M. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We obtain sufficient conditions for the convergence of the procedure of stochastic approximation for the diffusion process in the case of a uniformly ergodic semi-Markov process of switchings of the regression function with the use of a small parameter in the scheme of series.